Long-term Effect of Year-Round Tillage Patterns on Yield and Grain Quality of Wheat - Yonglu Tang; Xiaoli Wu; Chaosu Li; Chun Wu; Xiaoling Ma; Gang Huang (Plant Production Science, 2013)
A 7-year field experiment under a rice-wheat rotation system was conducted at Guanghan County in the Chengdu Plain of China from 2004 to investigate the long-term effect of different combinations of year-round tillage patterns and crop straw management on grain yield and quality of wheat. Treatments were rotary-till wheat + rotary-till rice without any straw (conventional treatment, CK), zero-till wheat with rice straw mulching + rotary-till rice with no wheat straw (WZRR), zero-till wheat with rice straw mulching + rotary-till rice with no wheat straw + autumn vegetable (WZRRV), zero-till wheat with rice straw mulching + zero-till rice with wheat straw mulching (WZRZ), and zero-till wheat with rice straw mulching + zero-till rice with wheat straw mulching under ridge-till (WRZB). There was little variation amongst years in grain yield and yield components with the treatment, while CK had lower yields in most years than other treatments with a slight decreasing trend; spike numbers per area had no significant change with the elapse of time. An obvious descending trend in grain number per spike and grains per area for CK and increase in 1000-grain weight for all treatments were observed; zero tillage and straw mulching improved wheat tiller ability, soil available nitrogen, phosphorus, and potassium contents at major growth stages, and leaf area index, SPAD, a portable chlorophyll meter reading, and dry matter at middle and late stages. Most grain quality traits of wheat were nearly the same in all treatments in all year-round tillage patterns.